Apinagia brejoagrestinensis (Podostemaceae): a new rheophyte from the Atlantic Forest of northeastern Brazil - Tavares, Aldaléa Sprada; Leite, Marcelo Sobral (Phytotaxa, 2015)
We describe and illustrate a new Podostemaceae species for the Atlantic Forest of northeastern Brazil: Apinagia brejoagrestinensis. Among the characteristics that separate this species from other congenerics are: flower arrangement, shape and number of tepals, and presence of trichomes on spathella and tepals. The latter characteristic is reported for the first time in the genus Apinagia. The new species is known through a single and small population restricted to a short reach of a dammed river with deforested margins, and so it is assumed to be vulnerable to extinction.